Acutaxylines A and B, two novel triterpenes from Dysoxylum acutangulum - Ismail, Intan Safinar; Nagakura, Yuta; Hirasawa, Yusuke; Hosoya, Takahiro; Mohd Lazim, Mohd Izwan; Lajis, Md. Nordin; Morita, Hiroshi (Pergamon Press, 2009)
Two novel triterpenes, acutaxylines A (1) and B (2) consisting of a cyclopentenone side chain at C-17 and an oxepan-2-ol, were isolated from the leaves of Dysoxylum acutangulum. The relative stereochemistry of 1 and 2 was determined by NOESY correlations. Acutaxyline B showed moderate cytotoxicity against human blood premyelocytic leukemia cells.